2018
DOI: 10.1039/c8dt01120f
|View full text |Cite
|
Sign up to set email alerts
|

The unsuspected influence of the pyridyl-triazole ligand isomerism upon the electronic properties of tricarbonyl rhenium complexes: an experimental and theoretical insight

Abstract: Two isomeric tricarbonyl rhenium(i) complexes, ReL1 and ReL2, that possess a 2-pyridyl-1,2,n-triazole (pyta) ligand (n = 4 and 3, respectively) connected to a 2-phenylbenzoxazole (PBO) moiety, were synthesized in good yields. The X-ray structures showed that in ReL1 the PBO moiety and the pyta ligand almost form a right angle hindering electron delocalization, while in ReL2 their nearly planar arrangement favors the electron delocalization in the whole organic ligand. Therefore, the nature of the ligand signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(46 citation statements)
references
References 77 publications
3
43
0
Order By: Relevance
“…Considering the OSWV cathodic part, both new complexes presented a reduction process beyond −1.8 V, as did ReL1. 8 This process was most likely attributed to the reduction of the PBO fragment, confirming that the latter is not involved in the complexation process. 14 Indeed, a similar reduction process was detected for both ligands L3 and L4 (Table S14, Fig.…”
Section: Electrochemical Propertiesmentioning
confidence: 81%
See 3 more Smart Citations
“…Considering the OSWV cathodic part, both new complexes presented a reduction process beyond −1.8 V, as did ReL1. 8 This process was most likely attributed to the reduction of the PBO fragment, confirming that the latter is not involved in the complexation process. 14 Indeed, a similar reduction process was detected for both ligands L3 and L4 (Table S14, Fig.…”
Section: Electrochemical Propertiesmentioning
confidence: 81%
“…It can be attributed to the reduction process of the substituted triazole ring whose potential value may substantially decrease by complexation as observed in related compounds. 13,15 Remarkably, the value of this first reduction process seems to be characteristic of this family of complexes incorporating a 2-pyridyl-1,2,4-triazole ligand 8 and could be related to the bent arrangement of the pyta and PBO moieties. In CV, the careful examination of the first reduction process at different scan rates showed that this process becomes quasireversible around 1 V s −1 for ReL3, as was the case for ReL1.…”
Section: Electrochemical Propertiesmentioning
confidence: 95%
See 2 more Smart Citations
“…In this regard, the copper(I) catalysed 1,3-dipolar cycloaddition of alkynes and azides to form 1,4-disubstituted-1,2,3-triazoles has become a popular transformation in the design of ligands for transition metal complexes over the past decade [5][6][7][8]. This has resulted in several reports on the preparation of 1,2,3-triazole-based rhenium(I) complexes [9][10][11][12][13][14][15][16][17][18][19][20], which have been applied for their therapeutical activity [21][22][23][24][25] and as luminescent biological imaging microscopy probes [26][27][28][29][30][31][32][33][34]. Recently, Ching et al reported a series of complexes of the form [Re(NˆN)(CO) 3 Cl], where the NˆN ligand is based on a 4-(pyrid-2-yl)-1,2,3-triazole framework [35].…”
Section: Introductionmentioning
confidence: 99%